Sistem Pendukung Keputusan Penentuan Prioritas Pemadaman Hotspot Kebakaran Hutan dan Lahan Menggunakan Metode Analytic Hierarchy Process dan Weighted Product - Aji Dwi Komara; Esmeralda C Djamal; Faiza Renaldi (Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Forest and land is a natural resource that is very potential to be used for national development. Nevertheless to forests and land are common threats and harassment that impede conservation efforts. One form of threats and harassment by the forest fires and land (karhutla). Land and forest fires in Indonesia is a problem that occurs regularly every year, especially during the dry season. Conventionally information delivery system is done by monitoring directly in the field, use a map and compass as well as the use of the gong in the villages as a tool to inform the public about the possibility of fire. Today, with the help of modern technology such as computers, telecommunications devices and the Internet many developing fire information system that provides information to map the locations of fire (hotspot). However, often the fire information display only hotspot in an area, featuring a fire-prone area served is not clear, and is not based on processing methods methodologically inconsistent, which tend to be subjective and dependent on the processing of data. Hotspot which appeared hundreds or even thousands, to minimize the danger of fire should be immediately sought a solution would have been to put it out, but by the number of hotspots that much is certainly not an easy thing to do. One determines the hotspot to be extinguished in advance will result in a more dangerous and greater losses. Planning activities for fire prevention and suppression requires accurate information, actual and easily understood by decision makers. Therefore, by utilizing advances in technology, it takes a Decision Support System (Decision Support System) to help determine hotspots land and forest fires are a top priority to extinguish based on the criteria that have been set. The proper method for application of the Analytic Hierarchy Process (AHP) and Weighted Product (WP).Â